Do Patients with Chronic Noncancer Pain Accept Treatment of Questionable Benefit More Readily that those Who Are Pain Free? - Mark K Simmonds; Saifee Rashiq; Philip Klemka; Alexander S Sclanachan (Pain Research and Management)
BACKGROUND: The efficacy of some common, questionable chronic pain interventions has been debated and it is unclear why sufferers of chronic noncancer pain agree to receive them. This study attempts to determine if chronic pain sufferers characteristically more readily accept treatment with questionable benefit.